2018
DOI: 10.4049/jimmunol.1800558
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effects of Respiratory Syncytial Virus–Induced Epithelial HMGB1 on Human Innate Immune Cell Activation

Abstract: High mobility group box 1 (HMGB1) is a multifunctional nuclear protein that translocates to the cytoplasm, and is subsequently released to the extracellular space during infection and injury. Once released it acts as a damage-associated molecular pattern and regulates immune and inflammatory responses. Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infections in infants and elderly, for which no effective treatment or vaccine is currently available. This study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…3G and 6H). In fact, pretreatment with a TLR4 blocking agent decreased the HMGB1 levels from virus-infected cells via the TLR4-NFκB pathway, and the inactivation of NFκB resulted in a decreased release of various pro-inflammatory cytokines, including IL-1β, IL-6, TNF-α and HMGB1 [37,54]. Furthermore, reduced HMGB1 levels led to the inhibition of NFκB pathway in various immune cells, and the inflammation response was alleviated significantly.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3G and 6H). In fact, pretreatment with a TLR4 blocking agent decreased the HMGB1 levels from virus-infected cells via the TLR4-NFκB pathway, and the inactivation of NFκB resulted in a decreased release of various pro-inflammatory cytokines, including IL-1β, IL-6, TNF-α and HMGB1 [37,54]. Furthermore, reduced HMGB1 levels led to the inhibition of NFκB pathway in various immune cells, and the inflammation response was alleviated significantly.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that TLR4 is key receptor of innate immune signaling responses to influenza virus and other respiratory viruses [51]. Although host HMGB1 and RAGE interaction is also a major mechanism driving serious liver injury, the TLR4 pathway has recently been demonstrated to be more involved in respiratory syncytial virus and human papilloma virus (HPV) infection [52][53][54]. Previously, the expression of TLR3, TLR4, TLR7, TLR9 and TLR10 genes from hepatic tissue was shown to be significantly upregulated in some viral infection models [32,55].…”
Section: Discussionmentioning
confidence: 99%
“…The biological implications of this mechanism may be of tremendous importance for the pathogenesis of severe pulmonary inflammation because the high constitutive cell surface RAGE expression. It has been demonstrated in preclinical and clinical studies that severe respiratory infections including influenza and human respiratory syncytial virus (HRSV) generate substantial extracellular HMGB1 release in pulmonary inflammation and that HMGB1-specific antagonists ameliorate these conditions (Ito et al 2011;Nosaka et al 2015;Nosaka et al 2018;Hatayama et al 2019;Manti et al 2018;Rayavara et al 2018;Rallabhandi et al 2012;Simpson et al 2020). Extracellular HMGB1 accumulates locally due to passive release from dying cells and active secretion from innate immunity cells and additional cell types.…”
Section: Ragementioning
confidence: 99%
“…Interestingly, many of these secreted proteins do not contain classic signal peptides, suggesting novel and incompletely understood mechanisms for innate signaling. For example, we have demonstrated that the nuclear damage-associated molecular patterns (DAMPs), HMGB1, and histone H3 undergo nuclear export and extracellular secretion in response to RSV; these DAMPs controlling mononuclear inflammation [38,41]. Informatics analysis indicated that RSV infected Scgb1a1-expressing bronchiolar cells selectively secrete 103 unique proteins and exosomal contents (Cluster 3 in Figure 1C).…”
Section: Nfκb Signaling In Bronchiolar Cells Generate Unique Innate Smentioning
confidence: 99%
“…Epithelial type I and III IFNs play an important role in anti-viral response of neighboring epithelial cells. Damage-associated HMGB1 is important in monocyte recruitment and activation [41]. Epithelial B-cell activating factor (BAFF) is responsible for T-cell independent B-cell activation mediating the pulmonary antibody response [42].…”
Section: The Role Of the Airway Epithelium In Innate Responses To Rsvmentioning
confidence: 99%